PREVALENSI KEJADIAN TINEA PEDIS DI RSUD DR RM DJOELHAM BINJAI PERIODE JANUARI TAHUN 2015 – DESEMBER TAHUN 2019 - HERVINA . (LP2MTBM MAKARIOZ, 2021)
Tinea pedis is a disease caused by fungal infection dermatofita that hits the skin on the toes, soles of the feet, and the lateralpart of the foot. Tinea pedis is often caused by Trichophyton rubrum. Age, gender and race are important epidemiologicalfactors, where the prevalence of tinea pedis infection in males is five times more than in females. This study is a descriptivestudy to describe the results of the examination of identification of patients tinea pedis. The population in this study were newall tinea pedis patients recorded in medical record data of Dr.RM Djoelham Binjai Hospital in January 2015 - December 2019that fit the inclusion criteria. Data collection using secondary data with total sampling techniques. It found that the prevalenceof tinea pedis patients was at most 31-50 years old, on average male gender as well as farmer's work.It is advised to thepatient to always maintain personal hygiene and moist and closed condition.